Managerialism in local government - Victoria, Australia - GRAMBERG, Bernadine Van; TEICHER, Julian (2000)
There has been a global phenomenon in public sector management which advocates a paradigm shift from administrative to managerial values. Governments have been able to put an ideological gloss on managerial strategies to suit local political agendas. The spread of this policy, where public servants have their roles transformed to managers and the public to costumers, serves to strengthen demonstration of the diminishing role of government and increasing reliance on the market. Through our research on managerialism in local government in Victoria, we show that there has been a rpackaging of the senior coucil manager into an idealised private sector version. However, we identify a paradox betwee the rhetoric of the empowered, entreprenerial "new public manager"and the reality of intensified government control and strutiny over municipal activities and conclude that "new public management"in Victorian local government is illusory or, at best, incomplete
Keywords: Managerialism, New Public Management; Local Government; Compulsory Competitive Tendering; Australia